Distribution characteristics of pulverized coal and stress–gas pressure–temperature response laws in coal and gas outburst under deep mining conditions. Issue 7 (29th March 2022) - Zhao, Bo; Wen, Guangcai; Ma, Qianwei; Sun, Haitao; Yan, Fazhi; Nian, Jun
Abstract: Deep mining will increase the likelihood of coal and gas outburst accidents and do harm to the safety of coal mining. In this study, a coal and gas outburst experiment under deep high‐stress conditions was carried out and stress–gas pressure–temperature response laws in coal and rock surrounding the burst hole were evaluated. The experimental results showed that the stress response around the burst hole was intense and stress variation decreased as distance from the position to burst port increased. The gas pressure in the coal decreased sharply and oscillated several times during the burst process. The maximum rebound range was 0.05 MPa during this process. The decreasing rate of gas pressure reduced with the increase of the position‐burst port distance. The temperature response near the burst port was stronger than peripheral area. The gas internal energy was still the main energy source of coal and gas outbursts, accounting for 75% of the total energy, and played a key role in the burst process. The contribution of elastic potential energy was 22% under deep high‐stress conditions in this study. Based on the analysis of burst energy, the gas and stress were key factors of an outburst. Abstract : 1. A coal and gas outburst experiment under high‐stress condition was carried out. 2. S–GP–T response laws surrounding the burst hole were evaluated. 3. The burst coal distribution characteristics were obtained.